2014
DOI: 10.1002/arp.1495
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Magnetic Survey of a Neolithic Causewayed Enclosure in West‐central France for the Interpretation of Archaeological Features

Abstract: This paper describes an interdisciplinary study of the Neolithic causewayed enclosure of Bellevue (Chenommet, France). Geophysical investigations and archaeological excavations were used alternately in order to optimize the acquisition of accurate data at different spatial scales: mapping of major structures was obtained by magnetic prospection of the whole site, while excavation identified small features weakly expressed in the prospecting results. Measurements of magnetic susceptibility and total magnetic fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
(17 reference statements)
0
16
0
1
Order By: Relevance
“…The magnetic signal is induced by the nature of the fill. An interdisciplinary study on the site of Bellevue showed that the internal ditches served as waste disposal zones (filled by ceramics, burned materials and others) which was the principal source of the high magnetic signal (Ard et al ., ).…”
Section: Presentation Of the Sitementioning
confidence: 97%
See 4 more Smart Citations
“…The magnetic signal is induced by the nature of the fill. An interdisciplinary study on the site of Bellevue showed that the internal ditches served as waste disposal zones (filled by ceramics, burned materials and others) which was the principal source of the high magnetic signal (Ard et al ., ).…”
Section: Presentation Of the Sitementioning
confidence: 97%
“…To make this correlation, a sweeping movement of the sensors was performed in the direction of a magnet. Thus, the mobile records the amplitude variation of the magnetic signal (linked to remoteness and becoming closer to the magnet) and the total station records this movement (Ard et al ., ; Lévêque & Mathé, ). A second synchronization phase was also applied between the mobile and base magnetometer.…”
Section: Devices and Data Acquisition Protocolmentioning
confidence: 99%
See 3 more Smart Citations